Anatomical root responses of rice to combined phosphorus and water stress - relations to tolerance and breeding opportunities - Bauw, P. de; Vandamme, Elke; Lupembe, A.; Mwakasege, L.; Senthilkumar, Kalimuthu; Drame, K.N.; Merckx, Roel (Commonwealth Scientific and Industrial Research Organisation, 2019)
Drought and low P availability are major limitations for rainfed rice (Oryza spp.) production. Root anatomy plays a key role in resource acquisition and tolerance to P and water limitations. Root anatomical responses of three contrasting rice varieties to combinations of different levels of P (deficient to non-limiting) and water availability (water stress to submergence) were evaluated in two pot trials. P availability was the dominant growth-limiting factor, but anatomical root responses to water availability were more prominent than responses to P availability. Cortical cell file number and number of xylem vessels decreased as a response to water stress, but stele and xylem diameter increased. Low P availability induced thinner xylem vessels and a thinner stele. Drought tolerance related to an overall thicker root stele, thicker xylem vessels and a larger water conductance. Some root traits were observed to be more responsive to water and P availability, whereas other traits were more robust to these environmental factors but highly determined by variety. The observed genotypic variation in root anatomy provides opportunities for trait-based breeding. The plasticity of several traits to multiple environmental factors highlights the need for strategic trait selection or breeding adapted to specific target environments.